2005
DOI: 10.1016/j.cub.2005.01.047
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis of Individual Differences in Phenylthiocarbamide and Propylthiouracil Bitterness Perception

Abstract: Individual differences in perception are ubiquitous within the chemical senses: taste, smell, and chemical somesthesis . A hypothesis of this fact states that polymorphisms in human sensory receptor genes could alter perception by coding for functionally distinct receptor types . We have previously reported evidence that sequence variants in a presumptive bitter receptor gene (hTAS2R38) correlate with differences in bitterness recognition of phenylthiocarbamide (PTC) . Here, we map individual psychogenomic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
756
2
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 631 publications
(811 citation statements)
references
References 20 publications
45
756
2
8
Order By: Relevance
“…9, left and middle panels). A comparison of functionally critical residues in selected TAS2R38 orthologs of the Euarchontoglires clade revealed that all of them invariantly exhibit amino acid residues characteristic for the human taster variant TAS2R38-PAV or a variation thereof (TAS2R38-PAI), which has been experimentally validated for full PTC/PROP responsiveness (33) (Fig. 9, right panel).…”
Section: Substancementioning
confidence: 91%
See 1 more Smart Citation
“…9, left and middle panels). A comparison of functionally critical residues in selected TAS2R38 orthologs of the Euarchontoglires clade revealed that all of them invariantly exhibit amino acid residues characteristic for the human taster variant TAS2R38-PAV or a variation thereof (TAS2R38-PAI), which has been experimentally validated for full PTC/PROP responsiveness (33) (Fig. 9, right panel).…”
Section: Substancementioning
confidence: 91%
“…In particular, exchanging tryptophan in position 201 for leucine or phenylalanine caused severely reduced PTC responsiveness and, practically, a loss of activation by PROP. Intriguingly, Trp-5.46 is found only in the haplorrhine primate clade including human and chimpanzee, which exhibit exquisitely PTC-as well as PROP-sensitive TAS2R38 receptors (33,66). Hence, it seems that PTC/PROP-sensitive TAS2R38 evolved within the Primate order in the haplorrhine branch.…”
Section: Substancementioning
confidence: 99%
“…Although PTC was first created in a chemistry laboratory and is probably not found in plants, there are many chemical relatives of PTC that stimulate the TAS2R38 bitter taste receptor. 39,46,47 At least one of these compounds is found in plant food (turnips), 48 and less similar but still related compounds are found in other plant species. 49 People with taster and nontaster alleles of TAS2R38 differ in their perception of vegetables (like watercress) that contain these PTC-like compounds.…”
Section: Bitter: Poisoned With Pleasurementioning
confidence: 99%
“…39 Other bitter molecules stimulate multiple receptors, and the loss of one may decrease but not eliminate the ability to detect that particular bitter molecule. 30,39,47,65-73 The perception of PTC is probably an extreme case of individual variation in bitter perception.…”
Section: Bitter: Poisoned With Pleasurementioning
confidence: 99%
“…Carriers of two insensitive alleles (AVI/AVI) are considered non-tasters, and those with at least one sensitive allele (PAV/AVI or PAV/PAV) are considered tasters. 16,17 Genetic analyses support the association between phenotypic taste blindness to PROP and smoking behaviors. For example, a population-based study showed that AVI homozygotes consumed more cigarettes/day than other genotypes.…”
Section: Original Investigationmentioning
confidence: 87%